The Exploration of Deli Malay Language Vowels: An Acoustic Phonetic Analysis - Syarfina, Tengku Syarfina; Zein, T. Thrhaya; Yusuf, Muhammad (Jurnal Arbitrer, 2024)
This study aims to discuss the acoustic profile of Deli Malay Language (Bahasa Melayu Deli) vowels from phonetics. In collecting data, the research will involve 15 DML native speakers. The speakers involved were between 20-40 years old. The data was obtained by recording the speaker’s voice in a quiet room with a consistent microphone distance of about 30 centimeters from the lips. Teak speakers will read syllable words containing target vowels in sentences with DML vowels. The pronunciation target vowel is placed on the first syllable. This study found that Deli Malay has seven vowels, namely vowels /i/, /e/, /ə/, /a/, /o/, /u/ and /ↄ/. DML vowel positions /i/ and /e/are high and medium front vowels. While the vowels /o/, /u/ and /ↄ/ are high and medium back vowels. Meanwhile, the vowels /a/ and / ə / are mid and low mid vowels. Later, this acoustic study calculated approximate vowel measurements based on F1 and F2 from the spectrogram at Praat. The measurement of the sound quality of forman vowels in Malay deli vowels is vowel /a/ F1 = 876 Hz and F2 = 1701 Hz vowel /i/ F1 = 533 Hz and F2 = 2328 Hz, vowel /e/ F1 = 689 Hz and F2 = 2204 Hz, vowels / ə/ F1= 692 Hz and F2= 1686 Hz, vowels /o/ F1= 650 Hz and F2= 1459 Hz, /ↄ/ F1= 658 Hz and F2= 1373 Hz, and /u/ F1= 524 Hz and F2 = 1383 Hz. This study provides a detailed analysis of the acoustic properties of Deli Malay vowels, contributing to a deeper understanding of the phonetic characteristics of the language. This can be valuable for linguists and researchers studying Malay languages and their phonetic systems.